The Effect of Information Asymmetry, Business Diversification on the Cost of Equity Capital with Managerial Ownership as a Moderating Variable - Nurul Intan Okci Pratiwi; Tettet Fitrijanti; Sony Devano (Budapest International Research and Critics University, 2021)
The purpose of this study was to examine the effect of information asymmetry and business diversification on the cost of equity capital. The research sample was obtained by 48 mining companies listed on the Indonesia Stock Exchange (IDX). This study uses verification research with a quantitative approach. The method of analysis is panel data regression. The results showed that information asymmetry had a positive effect on the cost of equity capital. Business diversification and managerial ownership have a negative effect on the cost of equity capital. Information asymmetry and business diversification moderated by managerial ownership affect the cost of equity capital. Firm size as a control variable has a positive effect on the cost of equity capital.